Novel carbocyclic nucleoside analogs suppress glomerular mesangial cells proliferation and matrix protein accumulation through ROS-dependent mechanism in the diabetic milieu. II. Acylhydrazone-functionalized pyrimidines. Issue 3 (1st February 2016) - Bouhadir, Kamal H.; Koubeissi, Ali; Mohsen, Fatima A.; El-Harakeh, Mira Diab; Cheaib, Rouba; Younes, Joan; Azzi, Georges; Eid, Assaad A.
Graphical abstract: Abstract: We report herein the synthesis of a novel series of carbocyclic acylhydrazone derivatives of uracil, thymine and cytosine from the corresponding nucleic bases and their biological activity to treat diabetic nephropathy. Intriguingly, five derivatives significantly reduced high-glucose induced glomerular mesangial cells proliferation and matrix protein accumulation in vitro. The anti-oxidative effects displayed by these molecules suggest that their activity might involve a ROS-dependent mechanism.